Fenomena Migran Wanita Sebagai Pedagang di Pasar Inpres Muara Enim - Sri Mardiawati; Rosmiyati Chodijah; Ridhah Taqwa (Master Program in Sociology, Faculty of Social and Political Science, Universitas Sriwijay, 2017)
The purpose of this study was to analyze the reasons of female migrant traders to Muara Enim and to trade in the Muara Enim Inpres Market. This research use qualitative approach with descriptive analysis method. Data collection of interview methods. The results of this study show why migrant women migrated to Muara Enim because of: economic reasons, social reasons and communication reasons. While the reasons for female migrant traders are trading in Muara Enim Inpres Market because of: family / kinship, income, close to residence and located in City Center. The limited income of women migrant traders in the area of origin makes them have to decide to migrate to Muara Enim, which they think is able to provide better income. Female migrant traders choose to trade in the Muara Enim Inpres Market due to family reasons that have been previously traded, better income, close to the residence of female migrant traders making it easier for trading activities and the reason for being in the City Center which is the reason migrant traders are trading in the Inpres Market Muara Enim.